OPTIMALISASI BIAYA PELAKSANAAN PEMBANGUNAN ADMINISTRATION BUILDING MENGGUNAKAN METODE VALUE ENGINEERING (Universitas Muhammadiyah Palembang, 2022)
Value Engineering is a multidisciplinary-based systematic approach that is carried out creatively,innovatively and systematically to find a functional balance between cost, reliability and performance toachieve the concept of value for money. In value engineering there are six stages. The information stagecarried out 2 analyzes, namely cost breakdown and Pareto diagram analysis, resulting in the largestwork being owned by concrete work with a weight of 37% and a weight of 28% of floor slab work fromthe total concrete work. The function analysis stage produces 1 primary function and 4 secondaryfunctions. The creative stage produces 3 creative ideas, namely the Conventional Method (PA-1),Floordeck and Wiremesh Method (PA-2), and Hollow Core Slab Method (PA-3). The evaluation stageresulted in 2 creative ideas that passed. In the development stage, several calculations are carried outthat support all creative ideas. In the evaluation criteria stage, each alternative choice is assessed withthe help of the Expert Choice application, resulting in a total PA-2 value of 20% greater than PA-1. Thecalculation of the floor slab design results in the serviceability of PA-2 being 12.67% higher than that ofPA-1. PA-1's NPV is 5% greater than PA-2's. The PA-2 index value is 2.17 smaller than PA-1. The use ofPA-2 can save RAB of IDR 101,372,430.00 or 5%.